Heparanase protects the heart against chemical or ischemia/reperfusion injury. (June 2019) - Wang, Fulong; Pulinilkunnil, Thomas; Flibotte, Stephane; Nislow, Corey; Vlodavsky, Israel; Hussein, Bahira; Rodrigues, Brian
Abstract: Although cancer cells use heparanase for tumor metastasis, favourable effects of heparanase have been reported in the management of Alzheimer's disease and diabetes. Indeed, we previously established a protective function for heparanase in the acutely diabetic heart, where it conferred cardiomyocyte resistance to oxidative stress and apoptosis by provoking changes in gene expression. In this study, we tested if overexpression of heparanase can protect the heart against chemically induced or ischemia/reperfusion (I/R) injury. Transcriptomic analysis of Hep-tg hearts reveal that 240 genes related to the stress response, immune response, cell death, and development were altered in a pro-survival direction encompassing genes promoting the unfolded protein response (UPR) and autophagy, as well as those protecting against oxidative stress. The observed UPR activation was adaptive and not apoptotic, was mediated by activation of ATF6α, and when combined with mTOR inhibition, induced autophagy. Subjecting wild type (WT) mice to increasing concentrations of the ER stress inducer thapsigargin evoked a transition from adaptive to apoptotic UPR, an effect that was attenuated in Hep-tg mouse hearts. Consistent with these observations, when exposed to I/R, the infarct size and markers of apoptosis were significantly lower in the Hep-tg heart compared to WT. Finally, UPR and autophagy inhibitors reduced the protective effects of heparanase overexpression during I/R. Our data suggest that the mechanisms that underlie the role of heparanase in promoting cell survival could be uniquely beneficial to the heart by providing protection against cellular stresses, and could be useful for exploitation as a therapeutic target for the treatment of heart disease. Graphical abstract: Unlabelled Image Highlights: Cardiac overexpression of heparanase upregulated pro-survival and catabolism genes. These gene changes contributed to activation of adaptive UPR and autophagy. Activation of ATF6α is a key initiator of adaptive UPR. Heparanase promotes autophagy by UPR activation and mTOR inhibition. These adaptations protected the heart against chemical and I/R induced injury.